Value of Assessing AMH in the Management of Polycystic Ovarian Syndrome (PCOS) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in reproductive age affecting 5 “ 10% of women and is the leading cause of ovulatory dysfunction. Anti-mullerian hormone (AMH) is a dimeric glycoprotein releases from the granulosa cells of small preantral and antral follicles and these concentrations have shown to be proportional to the number of developing follicles in the ovaries. In women with PCOS serum levels are elevated 2- to 3- fold in comparison with normo-ovulatory women, consistent with the increased number of small antral follicles in these women. AMH production per granulosa cell is increased on average 75-fold in anovulatory PCOS compared with normal ovaries. AMH is a marker for ovarian reserve of the women. It also can be used for diagnosis of PCOS. The high level of PCOS has negative effect on reproduction. It inhibits the function of FSH and causes follicular arrest and anovulation. In presence of high AMH there is poor response to oral ovulation inducing agent, gonadotropin and laparoscopic ovarian drilling. Quality of embryo, implantation rate and live birth rate are significantly reduced in presence of high AMH. High LH, hyperandrogenism, hyperinsulinemia have association with high AMH. Androgen is responsible for increasing the number of preantral follicles, hence AMH. Adjuvant therapy like metformin can correct hyperandrogenism, reduce the serum level of AMH and improve ovulation, pregnancy and live birth rate. Pre-treatment AMH level 7.77ng/ml is a cutoff level to predict the response to fertility treatment in PCOS. Ovulation, pregnancy and live birth rate are significantly lower when AMH level is >7.77ng/ml. So, to predict response to treatment and to fix the treatment plan value of assessment of AMH is important in case of PCOS.Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 47-62